Implementasi Manajemen Mutu Pendidikan di MA PERSIS Tarogong - Naqiya Salsabila (Idarotuna: Jurnal Manajemen Pendidikan Islam, 2026)
Educational quality is an important indicator in determining the success of Islamic educational institutions in producing competitive and qualified graduates. This study aims to analyze the implementation of educational quality management at MA PERSIS Tarogong in improving educational quality based on National Education Standards. This research employed a qualitative approach using a case study method. Data were collected through observation, interviews, and documentation involving the principal, teachers, educational staff, and institutional documents. The data were analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that the implementation of educational quality management at MA PERSIS Tarogong was carried out through management functions consisting of planning, organizing, actuating, and controlling in a systematic and sustainable manner. The application of Total Quality Management principles was reflected in the commitment to quality improvement, the involvement of all school members, and periodic program evaluation. The implementation of quality management contributed to improving learning quality, teacher competence, student achievement, and public trust in the institution. This study concludes that successful educational quality management requires visionary leadership, a strong quality culture, and synergy among all components of educational institutions.